Erectile dysfunction and lower urinary tract symptoms: a consensus on the importance of co‐diagnosis. Issue 7 (25th April 2013) - Kirby, M.; Chapple, C.; Jackson, G.; Eardley, I.; Edwards, D.; Hackett, G.; Ralph, D.; Rees, J.; Speakman, M.; Spinks, J.; Wylie, K.
Summary Despite differences in design, many large epidemiological studies using well‐powered multivariate analyses consistently provide overwhelming evidence of a link between erectile dysfunction (ED) and lower urinary tract symptoms (LUTS). Preclinical evidence suggests that several common pathophysiological mechanisms are involved in the development of both ED and LUTS. We recommend that patients seeking consultation for one condition should always be screened for the other condition. We propose that co‐diagnosis would ensure that patient management accounts for all possible co‐morbid and associated conditions. Medical, socio‐demographic and lifestyle risk factors can help to inform diagnoses and should be taken into consideration during the initial consultation. Awareness of risk factors may alert physicians to patients at risk of ED or LUTS and so allow them to manage patients accordingly; early diagnosis of ED in patients with LUTS, for example, could help reduce the risk of subsequent cardiovascular disease. Prescribing physicians should be aware of the sexual adverse effects of many treatments currently recommended for LUTS; sexual function should be evaluated prior to commencement of treatment, and monitored throughout treatment to ensure that the choice of drug is appropriate.